Analysis of Tribological and Thermo-Physical Properties of Surfactant-Modified Vegetable Oil-Based CuO Nano-Lubricants at Elevated Temperatures - An Experimental Study - Chacko Preno Koshy (Japanese Society of Tribologists, 2015)
Superior tribological properties of mineral oil based nano-lubricants in boundary/thin film lubrication are well established. However, in view of the environmental aspects, vegetable oils are more preferable and studies are being carried out to evaluate the performance of vegetable oils when nanoparticles are added to them. In this paper, behaviour of vegetable oils with the addition of Copper Oxide (CuO) nanoparticles is presented to evaluate their thermo-physical and tribological properties. Experimental studies at elevated temperatures are carried out on two base oils, viz., coconut and mustard oils as well as the nano-lubricants formulated from them by the addition of unmodified and surfactant-modified CuO nanoparticles separately. Enhancement of thermo-physical properties such as viscosity and fire-point is more pronounced for nano-lubricants containing surfactant-modified CuO nano-lubricants than the corresponding nano-lubricants containing unmodified CuO nanoparticles. Similar improvements in friction-reduction and anti-wear properties are also observed based on experiments conducted on a modified pin-on-disc tribometer at ambient and elevated temperatures. From the dispersion analysis it is seen that the nano-lubricant containing unmodified nanoparticles is not suitable for long stationary applications. Analyses of the pin surface before and after sliding with different nano-lubricants at the interface are carried out using Atomic Force Microscopy. The above analyses of the pin surface also show encouraging results with surfactant-modification of CuO nanoparticles in terms of the average surface roughness of the pin surface. The results from the current experimental study envisage the prominence of vegetable oil based nano-lubricants in the foreseeable renewable-based economy.